BIOSKOP DAN PUJASERA DI BANJARBARU - Muthiah Muthmainnah; Irma Fawzia (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The Indonesian cinema industry has shown significant growth with a total of 60 million viewers in 2024. However, this growth is still concentrated in the Java Island region. The government is working to build cinemas in various cities, including Banjarbaru, to improve industry equity. Currently, cinemas in South Kalimantan are located in shopping centers with relatively expensive ticket prices and limited facilities. Given these conditions, a combination of cinemas and dining areas such as food courts is needed through a hybrid approach with the